Inventarisasi Jenis Tumbuhan Pangan Lokal pada Masyarakat Ambaidiru Distrik Kosiwo, Kabupaten Yapen Waropen - Fali Sembori; Rosye H.R. Tanjung (Jurusan Biologi FMIPA Universitas Cenderawasih, 2009)
This study had aim to explore plant species which were used as local food by Ambaidiru people, which part of the plant and how they used, also what species that have been cultivated. This reseach was done from April – June 2007 using survey methods. The result showed that there were 54 species consist of 36 families of locally food source. Among them, 16 species categorized as fruit, 14 species as vegetable, and 5 species as fiber. Most of them were introduced species (74.1%), while the rest (25,9%) were local species, i.e. Passiflora foetida L. (Passifloraceae) and Pometia pinnata (Sapindaceae). Introduced plant species mostly have been cultivated by the local people. This was result of the long term cultural interaction between local people and the invader. Key words: local food plant, Ambaidiru people, Yapen Waropen